Essence of Schism (Old Belief) in Works and Sketches of Priests and Secular Figures of the Second Half of the XIX-XX Centuries - Gennadii Nikolaevich Khrapkov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
This article is devoted to the study and analysis of one of the most significant movements in the religious and social life of the population of the Russian Empire in the second quarter of the XVII century - old belief taking into account opinions and views of the clergy and secular figures of the second half of the XIX - XX centuries, presented in their works. The aim of the work is based on the analysis of sources and literature containing information about the wing of the old believers in the specified chronological framework in the country’s history, to present the most objective form that represented the split in the second half of XIX - early XX centuries, and to identify a number of characteristic features that distinguish the believers from the whips, the skoptsy, Molokans and other sects. For the writing of this article the author used the following methods: typological (analysis of estimates of the old believers in the writings of the clergy and the secular leaders of that era and the modern period), analytical (the desire to identify a number of factors, of differences, which allow you to make a more clear distinction between the old believers and sectarians), structural (an attempt to identify specific features of the activities performed by the canons and rites, common to all old believers pushing, allowing to present them as a single current of religious thought in the country). The result is identification as a characteristic that separates the believers from heretical teachings, and a number of factors, which conservatives referred to the sects in the modern period of time. The results of this work give a totally new direction in the study of a specified religious movements in Russia’s history when the need for a more detailed account and analysis of negative and positive evaluations of the researchers.